1883 Wis. Sess. Laws 1034, ch. 351, § 32, pt. 45 - (:unkn) unknown (My University, 1883)
Authorized the city to prohibit and prevent the concealed carry of any pistol, sling-shot, knuckles, Bowie knife, dirk knife, dirk, or dagger, or other dangerous or deadly weapon.
Keywords: CARRY - CONCEALED